Bebida mista industrializada de frutas e vegetais "detox" : caracterização química, potencial antioxidante e estudo da rotulagem geral e nutricional - Eliane Beatriz Magalhães Silva (2019)
The objective of this work was to determine the physicochemical composition, the content of antioxidant compounds and to characterize the chemical profile of industrialized mixed fruit and vegetable drinks. Conformity assessment of the general and nutritional labeling of these products was carried out, based on the requirements of current legislation. Seven mixed drink of fruits and vegetables of different brands with denomination "detox" juice were selected on the label. The physicochemical analyzes were moisture, protein, ashes, carbohydrates, titratable acidity, pH, soluble solids (°Brix) and ascorbic acid, following the AOAC methodology (2016). Lipid content was determined by the Bligh & Dyer extraction method. The phenolic compounds were determined by the Folin-Ciocalteu reducing capacity method, the antioxidant activity by the ABTS methods and the fingerprinting of the samples was performed using the PS-MS. The physicochemical composition of the samples presented statistical differences (p <0.05), probably associated with the different proportions of the ingredients present in each formulation. Total carbohydrate values ranged from 4.17% (sample D) to 12.72% (sample G), and drinks with lower values, brands B and C have only apple as the constituent fruit and (sample D ) was made with apple and orange. However, despite the presence of both fruits, the total solids value of (sample D) was 4.64% g / 100g, the lowest of all samples. Lipid and protein contents showed statistical differences, ranging from 0.04% (sample C) to 0.80% (sample F) and protein contents ranged from 0.07% (sample D) to 1.78% ( F), and the samples with the highest protein values were E, F and G, which had four common ingredients (pineapple, apple, ginger, cabbage). The pH values ranged from 3.02 (sample C) to 4.63 (sample D), presenting significant differences. Samples A, C, E, F and G showed a more acidic pH, which can be attributed to the presence of lemon and pineapple fruits in the beverage ingredients list. Total phenolic compound contents ranged from 26.75 mg AGE g-1 (sample F) to 48.61 mg AGE g-1 (sample D). Samples A, B and C contain in the ingredient list kale, spinach, parsley and presented significantly higher bioactive compound content than the other samples. The antioxidant capacity ranged from 1.76 µM trolox.g-1 (sample B) to 18.95 µM trolox.g-1 (sample E). The samples E, F and G that presented higher antioxidant potential and the common ingredients among the mixtures were pineapple, apple, kale and ginger. With the PS-MS mass spectrometric analysis it was possible to identify different types of compounds, belonging to the phenolic acids, triterpenes, furanones classes and others. Regarding the labeling analysis, nonconformities were observed in 100% of the samples due to the presence of the term “detox” on the label. Also noteworthy was the infringement in all samples due to the absence of registration with the Ministry of Agriculture, Livestock and Supply (MAPA) and the quantitative declaration of the percentage of juice on the label. Important bioactive compounds have been identified for human health and the nutritional labeling of these products needs to be adapted so that it can provide correct information to the consumer.